Behavioral detection of intra-cortical microstimulation in the primary and secondary auditory cortex of cats - Zhao, Zhenling; Liu, Yongchun; Ma, Lanlan; Sato, Yu; Qin, Ling (Frontiers in Systems Neuroscience, 2015)
Although neural responses to sound stimuli have been thoroughly investigated in various areas of the auditory cortex, the results electrophysiological recordings cannot establish a causal link between neural activation and brain function. Electrical microstimulation, which can selectively perturb neural activity in specific parts of the nervous system, is an important tool for exploring the organization and function of brain circuitry. To date, the studies describing the behavioral effects of electrical stimulation have largely been conducted in the primary auditory cortex. In this study, to investigate the potential differences in the effects of electrical stimulation on different cortical areas, we measured the behavioral performance of cats in detecting intra-cortical microstimulation (ICMS) delivered in the primary and secondary auditory fields (A1 and A2, respectively). After being trained to perform a Go/No-Go task cued by sounds, we found that cats could also learn to perform the task cued by ICMS; furthermore, the detection of the ICMS was similarly sensitive in A1 and A2. Presenting wideband noise together with ICMS substantially decreased the performance of cats in detecting ICMS in A1 and A2, consistent with a noise masking effect on the sensation elicited by the ICMS. In contrast, presenting ICMS with pure-tones in the spectral receptive field of the electrode-implanted cortical site reduced ICMS detection performance in A1 but not A2. Therefore, activation of A1 and A2 neurons may produce different qualities of sensation. Overall, our study revealed that ICMS-induced neural activity could be easily integrated into an animal’s behavioral decision process and had an implication for the development of cortical auditory prosthetics.